Zika Virus: Origins, Pathological Action, and Treatment Strategies - Gorshkov, Kirill; Shiryaev, Sergey A.; Fertel, Sophie; Lin, Yi-Wen; Huang, Chun-Teng; Pinto, Antonella; Farhy, Chen; Strongin, Alex Y.; Zheng, Wei; Terskikh, Alexey V. (Frontiers in Microbiology, 2019)
The Zika virus (ZIKV) global epidemic prompted the World Health Organization to declare it a 2016 Public Health Emergency of International Concern. The overwhelming experience over the past several years teaches us that ZIKV and the associated neurological complications represent a long-term world-wide challenge to public health. Although the number of ZIKV cases in the Western Hemisphere have dropped since 2016, the need for basic research and anti-ZIKV drug development remains strong. Re-emerging viruses like ZIKV are an ever-present threat in the 21st century where fast transcontinental travel lends itself to viral epidemics. Here, we first present the origin story for ZIKV and review the rapid progress researchers have made toward understanding of the ZIKV pathology and in the design, re-purposing, and testing - particularly in vivo - drug candidates for ZIKV prophylaxis and therapy ZIKV. Quite remarkably, a short, but intensive, drug-repurposing effort has already resulted in several readily available FDA-approved drugs that are capable of effectively combating the virus in infected adult mouse models and, most importantly, in both preventing maternal-fetal transmission and severe microcephaly in newborns in pregnant mouse models.